Analysis of Strengthening Steel Distribution Channel in Domestic Automotive Industry - Pangraksa, Sugeng; Djajadiningrat, Surna Tjahja (The Indonesian Journal of Business Administration, 2013)
Distribution has strategic role to spread up product from manufacturer into end-user. Automotive industry needs distribution channel which has: excellent data management, timely delivery management, excellent quality management, and competitive reducing cost. Krakatau Steel (KS) distributors has weaknesses to enter automotive market current that require tight prerequisite such as: consistency of product quality, good cooperation, close relationship, continuously cost reduction, wide spread to many vendors in small quantity consumption. This analysis using primary data from KSâ€™ customers and secondary data which come up from internal KS document, literature, text book and other analysis which are still relevant for this topic. Selecting appropriate distributor which fit to automotive requirement is a must in order to strengthen market position in automotive industry. Developing own coil center is new strategic decision that can be used as new core competence of Krakatau Steel.Â Keywords: consistency of quality product, excellent data management, timely delivery management, excellent quality management, and competitive reducing cost